2023
DOI: 10.21037/tlcr-23-171
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a predictive model for tumor mutation burden status based on CT radiomics and clinical features of non-small cell lung cancer patients

Abstract: Background Tumor mutation burden (TMB) is one of the biomarkers for efficacy of immune checkpoint inhibitors (ICIs) in non-small cell lung cancer (NSCLC). Due to the potential of radiomic signatures to identify microscopic genetic and molecular differences, thus radiomics is considered a suitable tool for judging the TMB status probably. In this paper, the radiomics method was applied to analyze the TMB status of NSCLC patients, so as to construct a prediction model for distinguishing between TMB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al reported associations between the absence of concavity, ill-defined border, less spiculation, normal adjacent bronchovascular bundle, and larger size of tumor that predict TMB-high NSCLC ( Zhang et al, 2020 ). A recent study divided these associations into radiomic signatures of intra-tumoral and peritumoral regions, in which the former performed better in distinguishing the TMB-high group ( Yang et al, 2023 ). Overall, these findings were in accordance with our findings with similar AUCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported associations between the absence of concavity, ill-defined border, less spiculation, normal adjacent bronchovascular bundle, and larger size of tumor that predict TMB-high NSCLC ( Zhang et al, 2020 ). A recent study divided these associations into radiomic signatures of intra-tumoral and peritumoral regions, in which the former performed better in distinguishing the TMB-high group ( Yang et al, 2023 ). Overall, these findings were in accordance with our findings with similar AUCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, insights that expand the cross-scale relevance to mutational loads of the whole genome are still limited. A plausible association has been reported between CT semantics ( Zhang et al, 2020 ) and radiomic signatures ( Yang et al, 2023 ) without the constant threshold of TMB and interracial validation.…”
Section: Introductionmentioning
confidence: 93%